PERAN PARTISIPASI ORANG MUDA KATOLIK DALAM KEHIDUPAN MENGGEREJA DI STASI WAIWADAN PAROKI SANTA MARIA GORETI - Margaretha Ema Tukan; Maria Rasita Ina Heli, Regina Priska Wea, Vinsensia Etmunda Nini Kelen, Alfonsus Mudi Aran (JOURNAL OF COMMUNITY DEDICATION, 2025)
This study aims to analyze the role and level of participation of young Catholics in church life at Waiwadan station. Using a descriptive qualitative research method, this study examines various forms of youth involvement in church activities, factors that influence their participation, and challenges faced in efforts to increase such participation. Data collection was conducted through in-depth interviews, field observations, and documentation studies involving young Catholics, church leaders, and local community leaders. At Waiwadan station, the problem faced by young Catholics is that they do not fully appreciate church life and spiritual life, so that some of them follow a worldly lifestyle rather than a spiritual lifestyle. Young Catholics are encouraged to participate in various church activities, which aim to arouse their enthusiasm in getting to know and deepening the Christian faith. The church is expected to provide attention and care in the apostolic task so that young people can live their faith. The research location was at Waiwadan station. The results of the study showed that the participation of young Catholics at Waiwadan station still needs to be improved in various aspects of church life. Some factors that influence their level of participation include understanding of faith, family support, youth development programs, and opportunities given to be actively involved in church services. This study recommends the need to develop more systematic development programs, improve intergenerational communication, and create a wider space for young people to actualize themselves in church life.